Eﬀectiveness of virtual reality cycling exercise towards the motoric and cardiorespiratory functions of post-stroke patients - Lesmana, I Putu Dody; Destarianto, Prawidya; Widiawan, Beni; Suryana, Arinda Lironika; Hossain, Fakir Sharif (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Virtual reality (VR) cycling exercise was developed as a physical rehabilitation therapy to impair the deﬁcit on motoric function and cardiorespiratory ﬁtness on post-stroke patients with lower extremity disorder. This study aims to determine the eﬀectiveness of VR cycling exercise towards the impairment of lower extremity motoric function and cardiorespiratory ﬁtness on post-stroke patients.Methods. This study engaged 15 people chosen through a purposive sampling method, who were divided into 8 intervention groups of post-stroke patients without comorbidities (post stroke 2 years) and 7 healthy people in a control group. The Fugl-Meyer assessment was used to decide the participation of the patients. To assess the lower extremity motoric functions, the timed up-and-go test (TUGT) was carried out, the 6-minute walking test (6-MWT) was conducted to assess the gait function and VO2max was tested to assess the cardiorespiratory ﬁtness. VR cycling exercise was conducted for 3 months, twice a week.Results. Both groups performed signiﬁcantly diﬀerently (p < 0.05) in terms of balance, gait ability, and cardiorespiratory ﬁtness. The decrease in the TUGT score and increase in the 6-MWT and VO2max test scores of the intervention group obtained after undergoing VR cycling exercise was signiﬁcantly bigger than it was before performing the exercise. The group of post-stroke patients was able to take the exercise in 40–60 min of each exercise period.Conclusions. VR cycling exercise is a highly eﬀective intervention to increase motoric function and cardiorespiratory ﬁtness in chronic post-stroke patients. Therefore, taking VR cycling exercise is recommended for stroke rehabilitation and clinical practice purposes.
Keywords: motoric function; cardiorespiratory ﬁtness; rehabilitation, stroke; virtual reality cycling